TAMAN HEWAN PELIHARAAN DAN TEATER KEBON JERUK - Judy Christiana Yeo; Petrus Rudi Kasimun (Jurusan Arsitektur dan Perencanaan, 2020)
People are always looking for something outside of what they find at home or at work. With the rapid population and economic growth in Indonesia, Jakarta has become one of the cities with the highest First and Second Place developments. The need for Third places is increasing to balance city growth as an alternative space. Companion animals can be a catalyst for several dimensions of personal and social relationships and interactions, to the formation of new friendships / communities. Given the increasing evidence of social isolation as a health risk factor, companion animals are an important factor in developing a healthy environment. Kebon Jeruk, West Jakarta has one of the most dominant First and Second Place developments. Based on survey results and analysis, as an area with one of the highest animal owners, this has hindered animal lovers from bringing their pets to public spaces safely and freely because of local regulations. Kebon Jeruk Pet Park and Theater is intended as a forum for residents of the surrounding population, for both animal lovers and other users that can intergrate basic Third place theories with programs suitable for the needs of housing residents, workers, students, and users of nearby health facilities that focuses on the relationship between humans and their pets to improve the quality of life both physically and mentally as well as increase public tolerance and knowledge of the benefits of pets on daily life. AbstrakManusia selalu mencari sesuatu di luar apa yang mereka temukan di rumah atau di tempat kerja. Dengan pesatnya pertumbuhan kependudukan dan ekonomi di Indonesia, Jakarta menjadi salah satu kota dengan pembangunan First Place dan Second Place yang tinggi. Kebutuhan akan Third place meningkat sebagai wadah alternatif dan penyeimbang pertumbuhan kota. Hewan pendamping dapat menjadi katalisator untuk beberapa dimensi hubungan dan interaksi personal dan sosial, hingga pembentukan persahabatan/komunitas baru. Mengingatnya semakin banyak bukti isolasi sosial sebagai faktor resiko kesehatan, hewan pendamping menjadi faktor penting dalam mengembangkan lingkungan yang sehat. Kebon Jeruk, Jakarta Barat sangat mendominasi dalam pembangunan First dan Second Place. Sebagai wilayah pemilikan hewan yang cukup tinggi, dari hasil survey dan analisis, hal ini menghambat para pecinta hewan karena peraturan setempat yang cenderung mengakibatkan para pemilik hewan untuk tidak dapat membawa hewan peliharaannya ke tempat umum secara aman dan leluasa. Taman Hewan Peliharaan dan Teater Kebon Jeruk ditujukan sebagai sebuah wadah untuk warga penduduk baik pecinta hewan maupun bukan di sekitarnya yang dapat menggabungkan teori dasar Third place dengan program yang sesuai untuk kebutuhan para penduduk perumahan, pekerja, mahasiswa/murid, dan pengguna fasilitas kesehatan sekitar yang berfokus pada hubungan antara manusia dengan hewan peliharaannya guna meningkatkan kualitas hidup dalam bentuk fisik maupun mental dan meningkatkan toleransi dan pengetahuan masyarakat akan manfaat hewan peliharaan terhadap kehidupan sehari-hari.